1966
DOI: 10.2307/1140970
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Identification of Human Seminal Stains

Abstract: conducting a survey of alcohol and road traffic problems in Grand Rapids, Michigan. Upon completion of this survey he returned to Michigan State University to pursue graduate work. The data reported herein are taken from a thesis submitted by Mr. Mischler in partial fulfillment of the requirements for the Master of Science Degree in Physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, it is reasonable to assume that proteins to which the antibody binds on the surface of the sperm head are denatured with increased temperatures. While the effective temperature range of the antibody in the SPERM HY‐LITER™ kit was not tested, serological stains have been observed to remain immunologically reactive after exposure to temperatures as high as 68°C (5). Our studies showed that extreme temperatures will affect the specificity of the antibody used in the kit.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is reasonable to assume that proteins to which the antibody binds on the surface of the sperm head are denatured with increased temperatures. While the effective temperature range of the antibody in the SPERM HY‐LITER™ kit was not tested, serological stains have been observed to remain immunologically reactive after exposure to temperatures as high as 68°C (5). Our studies showed that extreme temperatures will affect the specificity of the antibody used in the kit.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they are not completely specific to human semen. Conversely, the detection of spermatozoa in SAE is still widely considered confirmatory for the presence of semen (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Therefore, the identification of spermatozoa, and in particular sperm heads, in unknown biological stains is the most direct method of confirming the presence of semen on the item in question.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations